Peran PT. Permodalan Nasional Madani (PT.PNM) Dalam Mendukung Pertumbuhan UMKM Perempuan di Desa Bonjeruk, Jonggat, Lombok Tengah - Anjani, Baiq Tesa; Hailuddin, Hailuddin; Wijimulawiani, Baiq Saripta (Jurnal Konstanta, 2024)
This study aims to analyze "The Role of PT. Permodalan Nasional Madani (PT.PNM) in Supporting the Growth of Women-owned Micro, Small, and Medium Enterprises (MSMEs) in Bonjeruk Village, Jonggat District, Central Lombok". A qualitative research method was employed, utilizing observation, interviews, and documentation. Demographic, socioeconomic, financial, and intervention data from PNM were analyzed to understand the challenges faced by women-owned MSMEs and how PNM assists in overcoming these obstacles. The research findings indicate that the primary challenge faced by MSMEs is capital, and PNM has successfully provided quick solutions with uncomplicated requirements. PNM's mentoring activities encompass business capacity development programs, management services, and partnership programs. The conclusion of this research is that PT PNM plays a significant role in supporting the growth of women-owned MSMEs in Bonjeruk Village through the provision of capital and various business development programs. With this support, women-owned MSMEs can expand their businesses, improve their families' welfare, and contribute to the local economy.